Improvement in Poor Graft Function after Allogeneic Hematopoietic Stem Cell Transplantation upon Administration of Mesenchymal Stem Cells from Third-Party Donors: A Pilot Prospective Study. Issue 9 (September 2014) - Liu, Xiaodan; Wu, Meiqing; Peng, Yanwen; Chen, Xiaoyong; Sun, Jing; Huang, Fen; Fan, Zhiping; Zhou, Hongsheng; Wu, Xiuli; Yu, Guopan; Zhang, Xian; Li, Yonghua; et al.
Poor graft function (PGF) is a refractory complication that occurs after allogeneic hematopoietic stem cell transplantation (allo-HSCT). In the present study, we prospectively evaluated the efficacy and safety of mesenchymal stem cells (MSCs) expanded from the bone marrow of a third-party donor to patients with PGF after allo-HSCT. Twenty patients with PGF (7 with primary and 13 with secondary PGF) received MSCs (1 × 10 6 /kg) one to three times at 28-day intervals. Seventeen patients were responsive to MSCs, whereas three were not. Within the first 100 days after MSC treatment, 13 patients developed 20 episodes of infection. Moreover, five patients experienced cytomegalovirus-DNA viremia, and seven experienced Epstein—Barr virus (EBV)—DNA viremia within the first 100 days after MSC treatment; three of the latter developed EBV-associated posttransplant lymphoproliferative disorders (PTLD) within the follow-up period. Grade II acute graft-versus-host disease (GVHD) occurred in one patient, and local chronic GVHD occurred in two patients after receiving MSC treatment, including one acute GVHD and one chronic GVHD, respectively, after accepting donor lymphocyte infusions due to PTLD. After a follow-up period of an average of 508 days (range 166-904 days) posttransplantation, 11 patients died. No short-term toxic side effects were observed after MSC treatment. Two patients experienced leukemic relapse. With the exception of three patients with PTLD, no secondary tumors occurred. These results indicate that MSCs derived from the bone marrow of a third-party donor are beneficial in the treatment of both primary and secondary PGF that develops after allo-HSCT. However, additional studies will be needed to determine whether such treatment might increase the risk of EBV infection and reactivation or the development of EBV-associated PTLD.